STUDY OF INDUCTION AND DEDUCTION ISSUES BY PSYCHOLOGISTS (American Journal of Pedagogical and Educational Research, 2023)
In the article, the role of induction and deduction in the education of today's youth, the question of the role of thinking methods in knowledge, the fact that the problems of thinking have been out of the view of psychologists for a long time due to their complexity and the main reasons for this, the importance of the fact that philosophers and logicians think about the issue, the role of induction and deduction in the thinking process and the known Issues such as the emergence and solution of a problem, a problem, a puzzle are covered.